LOCATION OF KIPCHAQ ETHNOGRAPHIC GROUPS IN FERGANA VALLEY - Vakhobov Botirali Mikhailovich (Scholar Express Journal, 2022)
The article analyzes the time of penetration of ethnographic groups into the Fergana Valley according to the works of various researchers. It can be noted that the role of the valley's ethnographic groups in social, economic and political life was significant during the period under study. Of particular importance is the tribal division of ethnographic groups. The article attempts to highlight the ethnographic groups that make up the Uzbek people on the basis of historical and ethnological data
Keywords: Ethnographic group; assimilation process; consolidation; ethnic community